Lorcaserin Inhibit Glucose-Stimulated Insulin Secretion and Calcium Influx in Murine Pancreatic Islets - Jing, Muhan; Wang, Shanshan; Li, Ding; Wang, Zeyu; Li, Ziwen; Lu, Yichen; Sun, Tong; Qiu, Chen; Chen, Fang; Yu, Haijuan; Zhang, Wei (Frontiers in Pharmacology, 2021)
Lorcaserin is a serotonergic agonist specific to the 5-hydroxytryptamine 2c receptor (5-HT2CR) receptor that is FDA-approved for the long-term management of obesity with or without at least one weight-related comorbidity. Lorcaserin can restrain patients’ appetite, improve insulin sensitivity and hyperinsulinemia mainly through activating 5-HT2CR in the hypothalamus. It is known that the mCPP, a kind of 5-HT2CR agonist, decreases plasma insulin concentration in mice and previous research in our lab found that mCPP inhibited glucose stimulated insulin secretion (GSIS) by activating 5-HT2CR on the β cells. However, the effect of lorcaserin on GSIS of pancreatic β cell has not been studied so far. The present study found that 5-HT2CR was expressed in both mouse pancreatic β cells and β cell-derived MIN6 cells. Dose-dependent activation of 5-HT2CR by lorcaserin suppressed GSIS and SB242084 or knockdown of 5-HT2CR abolished the lorcaserin`s effect in vitro. Additionally, lorcaserin also suppressed GSIS in high fat diet (HFD)-fed mice in dose-dependent manner. Lorcaserin did not change insulin synthesis ATP content, but lorcaserin decrease cytosolic free calcium level ([Ca2+]i) in MIN6 cells stimulated with glucose and also inhibit insulin secretion and [Ca2+]i in MIN6 treated with potassium chloride. Furthermore, stimulation with the L-type channel agonist, Bay K8644 did not restore GSIS in MIN6 exposed to lorcaserin. Lorcaserin inhibits the cAMP generation of MIN6 cells and pretreatment with the Gα i/o inhibitor pertussis toxin (PTX), abolished lorcaserin-induced suppression of GSIS in β cells, while membrane-permeable cAMP analogue db-cAMP had same effect as PTX. These date indicated lorcaserin coupled to PTX-sensitive Gα i/o proteins in β cells reduced intracellular cAMP level and Ca2+ influx, thereby causing GSIS dysfunction of β cell. These results highlight a novel signaling mechanism of lorcaserin and provide valuable insights into the further investigation of 5-HT2CR functions in β-cell biology and it also provides guidance for the clinical application of lorcaserin.